Some aspects of the implementation of the release of material values during the reform of state reserves - Yu.M. Bilokon; O.V. Storozh (Економіка, управління та адміністрування)
The article explores issues related to the implementation of the main directions of state policy in the field of state reserve, aimed at reforming the existing system of the state reserve as an important component of the state security of Ukraine, taking place during the liquidation of the State Reserve Agency and activities, which are carried out to ensure this process, the temporary absence of a formed and capable central executive body, implementing state policy in the field of state reserves and solving problems with the coverage of material values of state reserves, in particular food products with a limited shelf life stored by responsible custodians. The lack of procedures established by the Cabinet of Ministers of Ukraine for carrying out operations with material values of state reserves, as provided for by the Law of Ukraine «On State Reserves», greatly complicates the situation. The authors of the article, based on the results of the analysis of the current legislation, proposed an algorithm of managerial activity aimed at practical solving the issue of issuing material assets from the state material reserve, in the conditions of reforming the state reserve system, eliminating the State Reserve Agency, the temporary absence of an executive body that implements a policy in the field of state reserves by making managerial decisions by executive authorities.